A utilização de códigos QR no combate à dissociação em coleções museológicas : o caso da reserva de escultura da Faculdade de Belas-Artes - Lopes, Guilherme Gameiro (2023)
This article presents a project for the management of the existing collection in the Sculpture Storage Room of the Faculty of Fine Arts of the University of Lisbon. After identifying the problems related to the dissociation factor in this collection, the use of QR codes is proposed to combat its consequences and to avoid future losses, with examples of sculptures from the plaster collection